CONCEPT OF “IMAGE” IN PHILOSOPHICAL ANTROPOLOGY - Сухомлин, Р. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the philosophical analysis of the concept "image" is conducted, and also its semantics in cultural and historical context is shown.